+0

# Solve for $x$: ​

0
124
3
+496

Solve for $x$: $$\dfrac{\sqrt{3x}-4\sqrt{3}}{\sqrt{x}-\sqrt{2}}=\dfrac{2\sqrt{2x}+\sqrt{2}}{\sqrt{6x}-2\sqrt{3}}$$

michaelcai  Sep 18, 2017
Sort:

### 3+0 Answers

#1
+17693
+1

I am going to try to simplify the denominators first.

The second denominator is  sqrt(6x) - 2·sqrt(3).

However, 2·sqrt(3) can be written as sqrt(4)·sqrt(3) = sqrt(12)

and sqrt(12) can be written as sqrt(6)·sqrt(2),

so sqrt(6x) - 2·sqrt(3) becomes sqrt(6)·sqrt(x) - sqrt(6)·sqrt(2),

and, factoring, becomes:  sqrt(6)[sqrt(x) - sqrt(2)].

This is almost the same as the first denominator, which is simply [sqrt(x) - sqrt(2)].

This means that if x = 2, these denominators are zero, so if we get an answer of 2, we'll have to throw it out.

Now, let's multiply both sides by sqrt(6)[sqrt(x) - sqrt(2)].

This cancels the denominator on the left side of the equation, but puts a factor of sqrt(6) on the left side.

This completely cancels the denominator on the right side of the equation.

We now have:  sqrt(6)·[sqrt(3x) - 4sqrt(3)]  =  2sqrt(2x) + sqrt(2)

Let's square both sides:

Left side:     [ sqrt(6)·[sqrt(3x) - 4sqrt(3)] ]2  = 6·[ sqrt(3x) - 4sqrt(3) ]2  =  6[ 3x - 2·4·sqrt(3x)·sqrt(3) + 16·3 ]

=  6[3x - 8·3·sqrt(x) + 48]  =  18x - 144sqrt(x) + 288

Right side:     [ 2sqrt(2x) + sqrt(2) ]2  =  4·2x + 2·2·2·sqrt(x) + 2

=  8x + 8sqrt(x) + 2

Setting these two equal:     18x - 144sqrt(x) + 288  =  8x + 8sqrt(x) + 2

Simplifying:     10x - 152sqrt(x) + 286 = 0

Dividing by 2:     5x - 76sqrt(x) + 143  =  0

Using the quadratic formula to find sqrt(x);     sqrt(x)  =  [ 76 +/1 sqrt(762 - 4·5·143) ] / 10

----->     sqrt(x)  =  13 or 2.2

----->     x = 169  or  x = 4.84

Checking both possible answers, 169 works but 4.84 is an extraneous root introduced by the squaring process.

geno3141  Sep 18, 2017
#2
+79735
+1

[ √[3x] - 4√3 ]   =   2√[2x] + √2

__________       __________

√x  - √2                 √[6x] - 2√3

[ √3 (√x - 4) ]  =  [ √2 ( 2√x + 1) ]

__________     _____________

√x  - √2               √[6x] -  √12

[ √3 (√x - 4) ]  =  [ √2 ( 2√x + 1) ]

__________     _____________

√x  - √2               √6 [ √x - √2 ]

[ √3 (√x - 4) ]  =  [ √2 ( 2√x + 1) ]

_____________

√6

[ √3 (√x - 4) ]  =  [ ( 2√x + 1) ] / √3

3[√x -  4]    =     2√x + 1

3√x - 12   =   2√x + 1

√x  =  13

x  = 169

CPhill  Sep 18, 2017
#3
0

Solve for x:
(sqrt(3) sqrt(x) - 4 sqrt(3))/(sqrt(x) - sqrt(2)) = (2 sqrt(2) sqrt(x) + sqrt(2))/(sqrt(6) sqrt(x) - 2 sqrt(3))

Cross multiply:
(sqrt(3) sqrt(x) - 4 sqrt(3)) (sqrt(6) sqrt(x) - 2 sqrt(3)) = (sqrt(x) - sqrt(2)) (2 sqrt(2) sqrt(x) + sqrt(2))

Subtract (sqrt(x) - sqrt(2)) (2 sqrt(2) sqrt(x) + sqrt(2)) from both sides:
(sqrt(3) sqrt(x) - 4 sqrt(3)) (sqrt(6) sqrt(x) - 2 sqrt(3)) - (sqrt(x) - sqrt(2)) (sqrt(2) + 2 sqrt(2) sqrt(x)) = 0

(sqrt(3) sqrt(x) - 4 sqrt(3)) (sqrt(6) sqrt(x) - 2 sqrt(3)) - (sqrt(x) - sqrt(2)) (sqrt(2) + 2 sqrt(2) sqrt(x)) = 26 + (-13 sqrt(2) - 2) sqrt(x) + sqrt(2) x:
26 + (-13 sqrt(2) - 2) sqrt(x) + sqrt(2) x = 0

Simplify and substitute y = sqrt(x).
26 + (-13 sqrt(2) - 2) sqrt(x) + sqrt(2) x = 26 + (-13 sqrt(2) - 2) sqrt(x) + sqrt(2) (sqrt(x))^2
= sqrt(2) y^2 + (-2 - 13 sqrt(2)) y + 26:
sqrt(2) y^2 + (-2 - 13 sqrt(2)) y + 26 = 0

The left hand side factors into a product with two terms:
(y - 13) (sqrt(2) y - 2) = 0

Split into two equations:
y - 13 = 0 or sqrt(2) y - 2 = 0

Add 13 to both sides:
y = 13 or sqrt(2) y - 2 = 0

Substitute back for y = sqrt(x):
sqrt(x) = 13 or sqrt(2) y - 2 = 0

Raise both sides to the power of two:
x = 169 or sqrt(2) y - 2 = 0

Add 2 to both sides:
x = 169 or sqrt(2) y = 2

Divide both sides by sqrt(2):
x = 169 or y = sqrt(2)

Substitute back for y = sqrt(x):
x = 169 or sqrt(x) = sqrt(2)

Raise both sides to the power of two:
x = 169 or x = 2

(sqrt(3) sqrt(x) - 4 sqrt(3))/(sqrt(x) - sqrt(2)) ⇒ (sqrt(3) sqrt(2) - 4 sqrt(3))/(sqrt(2) - sqrt(2)) = ∞^~
(2 sqrt(2) sqrt(x) + sqrt(2))/(sqrt(6) sqrt(x) - 2 sqrt(3)) ⇒ (sqrt(2) + 2 sqrt(2) sqrt(2))/(sqrt(6) sqrt(2) - 2 sqrt(3)) = ∞^~:
So this solution is incorrect

(sqrt(3) sqrt(x) - 4 sqrt(3))/(sqrt(x) - sqrt(2)) ⇒ (sqrt(3) sqrt(169) - 4 sqrt(3))/(sqrt(169) - sqrt(2)) = -(9 sqrt(3))/(sqrt(2) - 13) ≈ 1.34548
(2 sqrt(2) sqrt(x) + sqrt(2))/(sqrt(6) sqrt(x) - 2 sqrt(3)) ⇒ (sqrt(2) + 2 sqrt(2) sqrt(169))/(sqrt(6) sqrt(169) - 2 sqrt(3)) = (9 sqrt(6))/(13 sqrt(2) - 2) ≈ 1.34548:
So this solution is correct

x = 169 - Courtesy of Mathematica 11 - !!!!

Guest Sep 18, 2017

### 3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details